2018
DOI: 10.1167/iovs.17-23036
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-Linking With Riboflavin and UVA Regulates Hemangiogenesis and Lymphangiogenesis in Rats

Abstract: CXL treatment only temporarily inhibits corneal inflammatory-associated hemangiogenesis and lymphangiogenesis in vivo. Such insight suggests that future studies are warranted to develop novel CXL strategies with longer-lasting effectiveness in attenuating hemantic- and lymphatic-related corneal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a recent study by Zhu et al, it was observed that CXL inhibited angiogenesis and lymphangiogenesis for the first 7 days at the corneal vascularization area, but later on, CXL enhanced the effect of angiogenesis and lymphangiogenesis factors. 14 In the same study, it has also been shown that inflammatory cytokines are similarly increased in CXL performed corneas after a temporary suppression period. 14 Similarly, vascularization at the bleb border in our patient might be caused by a combination of CXL-induced proinflammatory cytokines and angiogenic factors.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a recent study by Zhu et al, it was observed that CXL inhibited angiogenesis and lymphangiogenesis for the first 7 days at the corneal vascularization area, but later on, CXL enhanced the effect of angiogenesis and lymphangiogenesis factors. 14 In the same study, it has also been shown that inflammatory cytokines are similarly increased in CXL performed corneas after a temporary suppression period. 14 Similarly, vascularization at the bleb border in our patient might be caused by a combination of CXL-induced proinflammatory cytokines and angiogenic factors.…”
Section: Discussionmentioning
confidence: 80%
“… 14 In the same study, it has also been shown that inflammatory cytokines are similarly increased in CXL performed corneas after a temporary suppression period. 14 Similarly, vascularization at the bleb border in our patient might be caused by a combination of CXL-induced proinflammatory cytokines and angiogenic factors.…”
Section: Discussionmentioning
confidence: 80%
“…Zhu et al showed the effectiveness of corneal collagen cross-linking with riboflavin and UVA in reducing damage of acute corneal inflammation. Although the procedure effectively suppresses the hemangiogenesis and lymphangiogenesis in the first week, elevated apoptotic cells, cytokine levels, and neovascularization markers were observed in the second week [52]. Considering the cellular damage caused by UVA light, continued damage during the healing process does not allow rapid recovery in the cornea.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Our previous study also indicates that compacted collagenous architecture possibly obstructs inflammatory cell infiltration. 10 However, the mechanism remains unknown that accounts for how a more compacted ECM impedes immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization was evaluated at 3, 7, and 14 days after suture emplacement using a slightly modified method described elsewhere. 10 Briefly, three photographs of each cornea were taken using a digital camera (EOS 5200D; Canon, Tokyo, Japan) under green light at 16 times magnification (10 corneas per group); 360 degree area of corneal new vessels was analyzed at the same magnification using ImageJ software. The area between the innermost new vessel and the limbus was defined as the vascularized area.…”
Section: Methodsmentioning
confidence: 99%